The use of Telenomus remus (Nixon, 1937) (Hymenoptera: Scelionidae) in the management of Spodoptera spp.: potential, challenges and major benefits - Colmenarez, Yelitza Coromoto [UNESP]; Babendreier, Dirk; Ferrer Wurst, Francisco Ramón; Vásquez-Freytez, Carlos Luis; de Freitas Bueno, Adeney (CABI Publishing, 2022)
Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae), also known as fall armyworm (FAW) is a polyphagous pest which can cause significant losses and is considered a global threat to different crops and a risk to food security. Currently, in maize, the pest is predominantly controlled by pesticides or transgenic events. However, the use of biological control agents is considered the most sustainable and preferred method of control, providing high effectiveness. Among the various natural enemies reported for FAW, the egg parasitoid Telenomus remus has gained most interest, and has been mass released against FAW in the Americas for many years. In addition to FAW, other armyworms of the genus Spodoptera often cause high crop damage and may be controlled using T. remus. Among other important aspects, this paper presents a review on T. remus mass rearing techniques, estimated costs of mass production, and release strategies. Due to the recent invasion of FAW in Africa, Asia, and Australia T. remus provides good opportunities for the establishment of an augmentative biological control program, reinforcing sustainable production of major crops such as maize in affected countries.